Dziesięć lat czynnej współpracy Biblioteki Uniwersyteckiej w Poznaniu z NUKAT-em - Praczyk-Jędrzejczak, Małgorzata; Świstek-Oborska, Bożena (Biblioteka Uniwersytecka w Poznaniu, 2015)
The article presents the initial access and input of the University Library to the Subject Heading Authority File, a controlled keyword descriptor system used for subject indexing in library catalogues, and then to the Central NUKAT Catalogue. The authors discuss procedures related to co-cataloguing within this system. A particular attention is given to the problems of formal and subject processing of documents. Solutions and arrangements worked out at the Library and aimed at streamlining the work of cataloguers are presented as well as the Library’s participation in projects and training sessions organized by NUKAT . Additionally, KA BA, the subject heading language used to describe publication subjects in Polish academic libraries, originated in the 1990s, is presented. The present article summarises the ten years of active cooperation with NUKAT , but also includes information on preparations and relevant works prior to its actual implementation.

W artykule przedstawiono proces przystąpienia Biblioteki Uniwersyteckiej w Poznaniu do współtworzenia Centralnej Kartoteki Haseł Wzorcowych, a potem katalogu centralnego NUKAT . Autorki omówiły procedury związane ze współkatalogowaniem. Szczególną uwagę poświęciły zagadnieniom opracowania formalnego i rzeczowego dokumentów. Zaprezentowały rozwiązania i ustalenia wewnętrzne Biblioteki Uniwersyteckiej usprawniające pracę katalogerów oraz jej udział w projektach i szkoleniach organizowanych przez NUKAT . Zaprezentowano również jhp KA BA powstały w latach 90. XX wieku, służący do opracowania przedmiotowego zbiorów w polskich bibliotekach akademickich. Artykuł podsumowuje dziesięć lat czynnej współpracy z NUKAT -em, ale stanowi również o okresie przygotowania do jej wdrożenia.
Ten years of active cooperation between Poznań University Library and NUKAT
Keywords: Biblioteka Uniwersytecka w Poznaniu; Poznań University Library; katalog centralny; central Catalogue; NUKAT; Centralna Kartoteka Haseł Wzorcowych; Subject Headings Authority File; język haseł przedmiotowych KABA; KABA subject heading language